(untitled) (Indian Journal of Animal Production and Management, 2013)
The proximate composition and sensory qualities of low fat chevon salamis prepared by incorporating 10% goat fat (GF) and three different levels of dietary fibers viz. wheat bran (WB) and oat bran (OB) added @2%, 3% fiber & 4% (T1, T2 & T3) respectively were evaluated in this study. WB and OB were added in such quantities that maintains equal proportion of dietary fiber in the product from either source. The control product contained 20 per cent GF with no added dietary fiber sources. The study revealed significant decrease in percent moisture, crude protein, ether extract and total ash contents along with the increased incorporation levels of dietary fibers in the treated formulations. Sensory evaluation chevon salamis showed significant decrease (P<0.01) in juiciness and tenderness scores in fiber enriched formulated products. Amongst the different formulations, T1 registered highest overall acceptability next to the control, suggesting its better suitability for preparation of low fat chevon salamis although other product formulations were also found to be acceptable.